EFEKTIFITAS KAMUS BAHASA ARAB BERBASIS APLIKASI ANDROID DALAM MENERJEMAHKAN QIRAAH - HASTANG, HASTANG (DIDAKTIKA, 2017)
This research aims to know how Arabic dictionary affective in translating Qiraah by using android application. This research used descriptive qualitative method. Meanwhile, the population of this research is the second semester academic year 2016/2017 with purposive sampling as a technique to collect the sample is PS 6. The data were collected by using test, observation, and interview. The instrument of this research is performance instrument, observation guidance, and interview guidance. The data collection have done from the result of this research would be analyzed by using qualitative data analyzed. The result of this research showed that 1). Based on the performance of the students in general were able to translate Qiraah that have been prepared. 2). The result of interview showed that the students easy to find out the meaning of each mufradat so that by using this method in translating the Arabic text at the previous meeting. As the result, this application is very helpful in translating.